Grain Sorghum Response to Water Supply and Environment - J. Broeckelman; G. J. Kluitenberg; K. Roozeboom; G. Cramer; Eric Adee; A. Schlegel; J. D. Holman; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2016)
Three grain sorghum hybrids were selected to compare under different water supply scenarios across Kansas. The environments ranged from dryland in western Kansas to dryland and irrigated in central and eastern Kansas. The three hybrids that were selected represent different sorghum genotypes used commercially. Looking at two situations from higher and lower yielding environments, hybrids 1 and 3 had different strategies to attain final yields. In the higher yielding environment, both grain harvest index (HI, expressed as the dry weight ratio of grain yield to plant biomass at maturity) and biomass were maximized for hybrid 1 and hybrid 2. In the lower yielding environment, their yields were similar, but hybrid 1 produced less biomass and had a greater HI. Hybrid 3 exhibited the opposite scenario in that environment: greater biomass production and smaller HI. Following these outcomes, grain sorghum hybrids use multiple strategies to produce grain yield in each environment. In high yielding environments though, plants need to maximize both biomass and efficiency in partitioning to grain.
Keywords: grain sorghum; yield; genotypes; environments